Anti-inflammatory and Antioxidant Effects of Selenium on Orbital Fibroblasts of Patients With Graves Ophthalmopathy. Issue 5 (26th March 2021) - Kim, Bo-Yeon; Jang, Sun-Young; Choi, Dug-Hyun; Jung, Chan-Hee; Mok, Ji-Oh; Kim, Chul-Hee
Abstract : Purpose: In the present study, the authors investigated the effects of selenium on inflammation, hyaluronan production, and oxidative stress in primary cultured orbital fibroblasts of patients with Graves ophthalmopathy (GO). Methods: Orbital adipose/connective tissue specimens were obtained during the course of orbital surgery for patients with GO (n = 7) and other noninflammatory problems (n = 5). After incubation with various concentrations of sodium selenite for 48 hours, supernatants from primary cultures were collected. Hyaluronan and cytokine levels were measured using commercially available enzyme-linked immunosorbent assay kits. To determine the effect of selenium on reactive oxygen species (ROS) production stimulated by H2 O2 (100 μM) for 30 minutes, the cells were pretreated with various concentrations of sodium selenite for 60 minutes. Results: Interleukin (IL)-6 and tumor necrosis factor-alpha levels were significantly higher in orbital fibroblasts of patients with GO than in orbital fibroblasts of control patients. Hyaluronan production was suppressed by selenium in cultured orbital fibroblasts of patients with GO. Inflammatory cytokines such as IL-1α, IL-8, and tumor necrosis factor-alpha were suppressed by selenium in cultured orbital fibroblasts of patients with GO. IL-1β and IL-6 were not suppressed by selenium in cultured orbital fibroblasts of patients with GO. Selenium pretreatment reduced intracellular ROS generation stimulated by H2 O2 in cultured orbital fibroblasts of patients with GO. Conclusions: In conclusion, hyaluronan production, inflammatory cytokines, and intracellular ROS generation were suppressed by selenium in cultured orbital fibroblasts of patients with GO. Several inflammatory cytokines may be suppressed by selenium in cultured orbital fibroblasts of patients with GO. This study provide the basis for use of selenium in the treatment of GO. Abstract : In this study, the authors found evidence that selenium can be used in the treatment of Graves ophthalmopathy by suppressing inflammatory cytokines and intracellular reactive oxygen species generation. Supplemental Digital Content is available in the text.